2009
DOI: 10.1111/j.1399-3038.2008.00807.x
|View full text |Cite
|
Sign up to set email alerts
|

Early intervention with suplatast tosilate for prophylaxis of pediatric atopic asthma: A pilot study

Abstract: The onset of asthma may be related to Th2 cytokine dominance at the time when food allergies occur several months after birth. This study investigated the effectiveness of early intervention with a Th2 cytokine inhibitor (suplatast tosilate) for prevention of asthma in infants with food allergies and atopic dermatitis. Suplatast tosilate dry syrup (6 mg/kg daily) or a histamine H(1)-blocker (ketotifen fumarate dry syrup: 0.06 mg/kg daily) was administered randomly to 53 infants with atopic dermatitis caused by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 31 publications
3
6
2
Order By: Relevance
“…It is well known that H 1 antihistamines inhibit histamine signal by their binding to H1R. Recently, Yoshihara et al investigated the effectiveness of early intervention with suplatast for prophylaxis of pediatric atopic asthma and compared the efficacy of suplatast with ketotifen, one of the H 1 antihistamines, and found that suplatast is more effective for the primary prevention of wheezing and asthma in children than ketotifen (57). Their findings can be explained by our data.…”
Section: Discussionsupporting
confidence: 66%
“…It is well known that H 1 antihistamines inhibit histamine signal by their binding to H1R. Recently, Yoshihara et al investigated the effectiveness of early intervention with suplatast for prophylaxis of pediatric atopic asthma and compared the efficacy of suplatast with ketotifen, one of the H 1 antihistamines, and found that suplatast is more effective for the primary prevention of wheezing and asthma in children than ketotifen (57). Their findings can be explained by our data.…”
Section: Discussionsupporting
confidence: 66%
“…We also demonstrated that FEX is the most effective agent in terms of the suppression of TARC and MDC production from CD14+ cells after Cry j 1 stimulation. This conclusion may be supported by the observation that FEX exerted a significant suppressive effect at a concentration of 250 ng/ml, which is almost equal to therapeutic blood levels [18], but other agents, AZE, KET and OXA, required higher concentrations (approximately 1.5–2 times higher) than their therapeutic blood levels [19,20,21]. …”
Section: Discussionsupporting
confidence: 58%
“…Suplatast tosilate has been reported to suppress IgE formation and eosinophil counts presumably through inhibition of Th2 cytokine in basic experiments and in several clinical studies in patients with atopic asthma [13][14][15][16][17][18][19][20]. However, no significant decreases in Th2-related parameters, such as the total IgE level and the eosinophil count, were observed after suplatast tosilate treatment even among the responders in this study.…”
Section: Il-4/il-12 Snps and Efficacy Of Suplatast Tosilate In Atopiccontrasting
confidence: 54%
“…This agent has been used as an adjunct to or in combination with topical anti-inflammatory and immunosuppressive agents and has been shown to reduce the requirements for these agents [11,12]. Suplatast tosilate has been referred to as a Th2 cytokine inhibitor because 1) it was discovered based on its capacity to suppress murine IgE formation without affecting cellular immune responses [13], 2) it suppressed IL-4 and IL-5 production by Th2 cells [14], 3) it suppressed allergic inflammation via indirect actions on Th2 cells as well as direct actions on eosinophils [15][16][17][18][19], and 4) it affected certain biomarkers such as Th1/Th2 ratio during the treatment of allergic asthmatic patients [20]. Although its mechanism of action remains to be identified at a molecular level, it is reasonable to assume that its efficacy in allergic patients may be ascribed to the modulation of the Th2-related immune and inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%